1989
DOI: 10.1002/ccd.1810160205
|View full text |Cite
|
Sign up to set email alerts
|

Angina and vasospasm at rest in a patient with an anomalous left coronary system

Abstract: An anomalous left main coronary artery with passage between the right ventricular infundibulum and aortic root has been incriminated as the causation of sudden death in a small number of individuals, many of whom are quite young. Mechanical features such as angulation and compression are most often incriminated. A 59-year-old man with such a coronary anomaly who had chest pain at rest, ST segment elevation, and ventricular tachycardia, but who had no evidence of effort-related myocardial ischemia, is reported.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Unfortunately, in clinical practice, none of these have been shown to be useful in the prognostic assessment of SD and there are no prognostically distinguishing pathological features that could be prospectively defined (7)(8)(9)(10). Finally, another theory postulates that compression and kinking of the anomalous artery could cause intimal damage and a propensity to spasm and ischemia (39,40), which was described more than 20 years ago, but considered implausible by the majority (8,41).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, in clinical practice, none of these have been shown to be useful in the prognostic assessment of SD and there are no prognostically distinguishing pathological features that could be prospectively defined (7)(8)(9)(10). Finally, another theory postulates that compression and kinking of the anomalous artery could cause intimal damage and a propensity to spasm and ischemia (39,40), which was described more than 20 years ago, but considered implausible by the majority (8,41).…”
Section: Discussionmentioning
confidence: 99%
“…Some reports suggest that coronary anomaly predisposes to coronary spasm. [15][16][17] However, the angiographic images showed that the RCA was compressed from the outside, and the compression was not relieved with intracoronary nitroglycerin.…”
Section: Discussionmentioning
confidence: 99%
“…32,33 Finally, in some cases, the ischemia may be caused by vasospasm as a consequence of repeated endothelial injury of the anomalous coronary artery. 25,34,35 Although an anomalous coronary artery originating from the contralateral coronary sinus may carry similar complications regardless of whether the right or left coronary is involved, sudden death rates differ between the two because of the different regions of the heart that they each perfuse. Also, there is a higher risk of sudden death in cases where the anomalous coronary artery is dominant.…”
Section: Anomalous Origin From the Opposite Sinus Of Valsalvamentioning
confidence: 99%